1990
DOI: 10.1002/jez.1402550210
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro culture system for studying vitellogenin uptake into ovarian follicles of the rainbow trout, Salmo gairdneri

Abstract: The development of a short-term culture system to study vitellogenin (VTG) sequestration in vitro into vitellogenic follicles of the rainbow trout, Salmo gairdneri, is described.The outer epithelial cell layer of the trout follicle restricted VTG uptake considerably and its removal was a prerequisite to study VTG uptake in vitro. Vitellogenic follicles divested of the surface epithelium sequestered VTG at rates of up to 170 ngmm2 follicle surface-1.h-1(ng.mm-2.h-1). Uptake of VTG over an 8 h period of incub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 25 publications
1
26
0
1
Order By: Relevance
“…Preliminary evidence suggests that in teleosts, as in mammals, growth factors play an integral role in oocyte growth. For example, insulin has been shown to stimulate VTG uptake in rainbow trout follicles (Tyler et al, 1987;Shibata et al, 1993), an effect that may well be mediated through the IGF receptor, rather than the receptor for insulin itself. Indeed, there is considerable structural homology between the insulin receptor and IGF-I receptor (Scavo, 1991).…”
Section: Growth Factorsmentioning
confidence: 99%
“…Preliminary evidence suggests that in teleosts, as in mammals, growth factors play an integral role in oocyte growth. For example, insulin has been shown to stimulate VTG uptake in rainbow trout follicles (Tyler et al, 1987;Shibata et al, 1993), an effect that may well be mediated through the IGF receptor, rather than the receptor for insulin itself. Indeed, there is considerable structural homology between the insulin receptor and IGF-I receptor (Scavo, 1991).…”
Section: Growth Factorsmentioning
confidence: 99%
“…Furthermore, the existence of a new system of multiple Vtgrs that disparately bind functionally different types of Vtgs in white perch has been suggested [16]. Short-term in vitro studies have reported successful incorporation of radiolabeled Vtg into fish oocytes [17,18]. Several publications have explored the signals controlling Vtg uptake and suggest control by various hormones including gonadotropin I [19], insulin (INS) and thyroxine [20], a pituitary glycoprotein fraction from salmon [21], 11-ketotestosterone (11-KT), and INS-like growth factor hormone I (IGF-I) [22].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro culture systems have been developed for studies on VT sequestration into vitellogenic follicles of rainbow trout (Oncorhynchus mykiss) and F. heteroclitus, and have been used to demonstrate receptor-mediated VT incorporation by these oocytes (Tyler et al 1990;Kanungo et al 1990;Tyler 1991). The binding for VT was characterized in isolated oocyte membranes of the tilapia, Oreochromis niloticus (Chan et al 1991).…”
Section: B Hormonal Regulation Of Vitellogenin Uptake and Egg Membramentioning
confidence: 99%